Ultrasound‐Guided Percutaneous Peripheral Nerve Stimulation for the Treatment of Lower Extremity Pain: A Rare Case Report. Issue 8 (7th July 2019) - Ferreira‐Dos‐Santos, Guilherme; Hurdle, Mark Friedrich B.; Gupta, Sahil; Clendenen, Steven R.
Abstract: Objective: This case report presents an application of percutaneous peripheral nerve stimulation to the right superficial peroneal nerve to treat a patient with chronic intractable L5–S1 radiculopathy pain that conventional treatment failed to ameliorate. Methods: The patient underwent an uneventful implantation of a percutaneous peripheral nerve stimulator. The implanted lead (15 cm in length and 1.2 mm in diameter) containing the receiver coil and 3 stimulation electrodes (Bioness Stimrouter ®, Valencia, CA, U.S.A.) was implanted parallel with the trajectory of the right superficial peroneal nerve. Results: Two weeks after implantation of the percutaneous peripheral nerve stimulator, the patient experienced excellent pain relief and reported a significant increase in mobility. At the 3‐month follow‐up consultation, the patient reported maintenance of the reduction of pain in his right lower extremity as well as improved performance in his daily activities. Conclusion: Percutaneous peripheral nerve stimulation offers an alternative treatment option for intractable pain associated with chronic radiculopathy, especially for patients in whom conventional treatment options have been exhausted. Further clinical series involving larger numbers of patients are warranted in order to assess the definitive role of percutaneous peripheral nerve stimulation for the treatment of chronic intractable radiculopathy pain.